BS EN IEC 61162-460 ED3. Maritime navigation and radiocommunication equipment and systems. Digital interfaces. Part 460. Multiple talkers and multiple listeners. Ethernet interconnection. Safety and security (12th January 2022) - British Standards Institution,
No abstract available